Estudo morfodinâmico da praia de Ponta Negra, Natal/RN - Medeiros, Cristiane Sara de (2015)
The coastline is undoubtedly one of the most dynamic features of the planet. Its position in space is constantly changing in various time scales. The shoreline position is affected by a very large number of factors, some of natural origin and intrinsically related to coastal dynamics (balance of sediments, the relative sea level variations, dispersion of sediments, etc), and other related human interventions in the coastal zone. So to the survey, there were some signs of erosion along the Ponta Negra beach. The study site is a major driver of the city's economy, both in the formal economy, and in informal, and it shows the most popular urban beach of tourists and the local population. The scenic landscape of potential attracted the investment of travel and public enterprises, which did not consider the coastal dynamics present, and with the lack of basic services infrastructure (many illegal sewage connected the rainwater galleries) have caused negative impacts and consequences to the environment . Thinking about the lack of studies involving this issue and the importance of the beach to the city, this work had the main objective to characterize and understand the morphodynamics of Ponta Negra beach, or see how the morphological transformations occur from the beach according to seasonality climate and Navy during the period from May 2013 to April 2014 in three monitoring points. For this, we used technical procedures involving field steps: environmental characterization (characterization of the two major compartments praial gifts-shoreface and estirâncio), surveying and consolidate the three points, hydrodynamic data (section 02) wave height, period wave, speed of longshore current and laboratory steps (fineness of calcium carbonate content and organic matter content). We also calculated the Dean parameter and the volume of sediment carried by the coastal current in point 02. In the monitoring points, the Point 01 showed less erosivity and greater depositional predominance of sandy sediments, with the negative sediment budget just at the point 03, and it was found that the urban infrastructure (promenade) is taking up the post beach making with the mechanical force of the waves and the presence of storm sewers with underground sewerage connections cause erosion and destruction of the boardwalk on the beachfront. Section 02 was classified as dissipative state for each month. Thus it is believed that the study will serve as support for further research in coastal areas, since the data can be used for comparative studies and also interested in further understanding of this area is of great social, political and environmental.